Rapid antibody testing for SARS-CoV-2 vaccine response in pediatric healthcare workers. (December 2021) - Heyming, Theodore W.; Nugent, Diane; Tongol, Aprille; Knudsen-Robbins, Chloe; Hoang, Janet; Schomberg, John; Bacon, Kellie; Lara, Bryan; Sanger, Terence
Highlights: SARS-CoV-2 rapid antibody testing was found to correlate with neutralizing antibody ELISAs. Rapid antibody testing may be used to screen for the humoral vaccination response. Pediatric healthcare workers showed low rates of historical coronavirus infection. Abstract: Background: The durability of the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination remains unknown. The objective of this study was to evaluate a rapid SARS-CoV-2 IgM/IgG antibody detection kit as a qualitative screen for the humoral response to vaccination. Methods: Study participants ( n = 125) included pediatric healthcare workers (HCWs) who had received two doses of BNT162b2 or mRNA-1273. Participants were tested on study entry (March 12, 2021 to April 9, 2021). The mean number of days post second dose was 22 (range 17–36). Participants were tested for IgM/IgG antibodies to the SARS-CoV-2 spike protein with the RightSign COVID-19 IgG/IgM Rapid Test Cassette. ELISA/competitive inhibition ELISA (CI-ELISA) were subsequently run to assess for the neutralization effect and SARS-CoV-2 anti-nucleocapsid IgM/IgG antibodies. Results: Overall, 98.4% of participants were IgG-positive and 0.8% were IgM-positive on rapid RightSign testing. Of those with IgG-positive results, 100% were anti-spike protein IgG-positive on CI-ELISA; none of those who tested IgG-negative via the rapid test were IgG-positive on CI-ELISA. All HCWs who tested RightSign positive demonstrated neutralizing capability on CI-ELISA. Overall, 1.6% demonstrated anti-nucleocapsid IgM antibodies and 5.6% demonstrated anti-nucleocapsid IgG antibodies. Conclusions: The strong agreement between the rapid RightSign IgG results and confirmatory CI-ELISA testing suggests that this test may be used to assess for positive, and neutralizing, antibody responses to SARS-CoV-2 mRNA vaccination.